Civic Agency in Africa - Ebenezer Obadare, Wendy Willems (James Currey, 2014)
The search for meaning in today’s African politics involves a dual exercise: an understanding of the nature of power and an exploration of the ways and byways of resistance to power. The former entails a reconsideration of the manner in which power is understood and exercised on the continent. The latter implies the use of methodologies capable of making sense of the behaviour of political actors. The standard approach to these questions has conceptualised power in terms of the state and resistance in terms of civil society – the one being the converse of the other. Much energy has thus been devoted to an analysis of the post-colonial state and to an investigation of the specific texture of civil society inAfrica.This conceptual journeyhas yielded useful conclusions but it has suffered fromone fundamental defect: the propensity to define state and civil society with reference to the politics of theWest. Yet the analytical limits of this Western bias in the political analysis of postindependence Africa have all too often been exposed. As a result, the most recent scholarship has suggested that the state should be approached from a different, more local, angle and has conceded that the concept of civil society extant fails to explain the workings of societal resistance to the social, political and economic pressure underwhich Africans live andwork.1 The most fruitful way of explaining how we can get a better grip on contemporary African politics is to tackle these questions from the perspective of the ‘informal’ and of ‘agency’. But how can we conceptualise these two notions froman African rather thanWestern perspective? In order to do that, we should start fromwhat can be observed on the ground rather than fromthe categories employed byWestern political theories.2 If it is undoubtedly true that the state remains the preeminent actor in African politics,what is at stake here is the question of what the state actually is – that is,what are its boundaries and howit operates.The key here is to relate the state to the exercise of power. On the one hand, the state is constructed upon, andworks according to, a formal institutional logic,which has its origins in theWestern liberal or the Eastern authoritarian template. The state does what it was intended to do, namely aggregate and legitimise the exercise of power by the political elitewho are deemed to embody legitimate sovereignty. On the other hand, the states operates according to what are best defined as informal codes, which reflect the ways in which the relations between rulers and ruled actually operate. Here, the realities of legitimacy, representation and accountability refer to a separate,more subterranean, exercise of power shaped by the nature of the politics binding the political elite to the population, which sanctions their actions.